Experimental and theoretical studies of Palladium-hydrazide complexes' interaction with DNA and BSA, in vitro cytotoxicity activity and plasmid cleavage ability. (April 2021) - Karami, Kazem; Jamshidian, Nasrin; Zakariazadeh, Mostafa; Momtazi-Borojeni, Amir Abbas; Abdollahi, Elham; Amirghofran, Zahra; Shahpiri, Azar; Nasab, Akram Kazemi
Graphical abstract: Highlights: New Palladium (II) - Hydrazide complexes have been synthesized and fully characterized by spectroscopic methods. Biomacromolecules' interaction of synthesized compounds have been investigated by several spectroscopic methods. Molecular docking have been done for theoretical investigation of biomacromolecules' interaction with synthesized compounds. Effect of synthesized compounds on colon carcinoma (CT26) and breast cancer (4T1) cancer cell lines have been studied. PUC57 plasmid DNA have been used for investigation of cleavage ability of synthesized compounds. Abstract: New palladium complexes with general formula trans -[Pd(L)2 (OAc)2 ] (1, 2), (L = Benzhydrazide and 2-Furoic hydrazide) have been synthesized and characterized with various methods including elemental analysis, FT-IR, 1 HNMR and mass spectroscopy. Afterward their interactions with bovine serum albumin and calf thymus deoxyribonucleic acid have been investigated by UV–vis absorption, fluorescence emission and circular dichroism spectroscopy. Also, site‐selective replacement experiments with site probes have been carried out. Analysis of fluorescence spectrum indicated static quenching mechanism. Spectroscopic measurements for DNA binding showed the groove binding to DNA for both complexes. Furthermore, cytotoxicity studies of complexes and cis -platin have been done against colon carcinoma (CT26) and breast cancer (4T1) cell lines. Evaluation of complexes (1) and (2) on induction of apoptosis in CT26 cells has been done. Finally, plasmid cleavage ability of (1) and (2) was investigated by gel electrophoresis that indicate the more activity of (1) than (2).